Proximization as a Cognitive Mechanism in the Construction of Political Threat - Priadi, Arum (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
This study investigates how political discourse constructs a sense of threat through the cognitive–pragmatic process of proximization. Addressing the methodological gap in Critical Discourse Studies (CDS), it integrates Proximization Theory with Discourse Space Theory (DST) to explain how linguistic strategies collapse symbolic distance and legitimize political action. DST provides the socio-cognitive framework through which proximization operates along spatial, temporal, and axiological dimensions. Using a socio-cognitive discourse-analytic design, the study analyzes a political speech by Benjamin Netanyahu (UN General Assembly, 2025), coding each clause for its proximization function. Statistical results (χ²(2) = 25.47, p < .001) indicate a non-random distribution of proximization markers, dominated by axiological cues. These findings demonstrate that spatial contraction, temporal acceleration, and moral intensification jointly construct a trajectory moving the “Other” toward the deictic center, thereby reinforcing ideological alignment and legitimizing political intervention. The study contributes theoretically by integrating DST and proximization into a unified model of ideological cognition, methodologically by combining qualitative mapping and quantitative validation, and practically by illuminating how political actors linguistically manage perception of threat and legitimacy in global diplomacy.